Humoral and cell-mediated immune response to the third dose of BNT162b2 anti-SARS-CoV-2 vaccine in patients with cancer on active treatment: Focus on wild type, Delta and Omicron strains - Lasagna, Angioletta; Cassaniti, Irene; Bergami, Federica; Lilleri, Daniele; Percivalle, Elena; Quaccini, Mattia; Alessio, Niccolò; Comolli, Giuditta; Sarasini, Antonella; Camilla, Josè; Ferrari, Alessandro; Arena, Francesca; et al. (Journal of clinical oncology, 2022)
e13505Background: Although a full course of COVID-19 vaccine is effective in cancer patients, the duration of the protection and the efficacy of a booster dose against the new variants remain unknown. We prospectively evaluated the immunogenicity of the third dose of the SARS-CoV-2 BNT162b2 mRNA vaccine in cancer patients undergoing active treatment. Methods: Patients with solid cancer, vaccinated with a booster dose during active treatment, were prospectively enrolled in this study. Patients were classified in SARS-CoV-2 naïve (without previous COVID-19 infection) and SARS-CoV-2 experienced (with previous COVID-19 infection). Neutralizing antibody (NT Abs) titer and total anti-Spike IgG concentration were quantified in serum. Heparinized whole blood samples were used for SARS-CoV-2 Interferon Gamma Release Assay (IGRA). The primary endpoint was to assess the increase of IgG antibody level between baseline (T0) and 3 weeks after the booster (T1). Results: 142 consecutive patients were recruited. In SARS-CoV-2 naïve subjects, median level of IgG was 157 BAU/mL (interquartile range (IQR) 62-423) at T0 and reached median of 2080 (IQR 2080-2080) at three weeks after booster administration (T1; p < 0.0001). A median 16-fold increase of SARS-CoV-2 NT Abs titre (IQR 4-32) was observed in naïve subjects (from median 20 IQR 10-40 to median 640 IQR 160-640; p < 0.0001). Median IFN-γ level at T1 was significantly higher than that measured at T0 in SARS-CoV-2 naïve subjects (p = 0.0049) but not in SARS-CoV-2 experienced patients. No difference was observed in terms of median response between patients treated with immunotherapy and chemotherapy (p > 0.05). A stronger correlation between SARS-CoV-2 NT Abs and total IgG level was observed at T0 (r = 0.76; p < 0.0001) compared to T1 (r = 0.27, p = 0.0081). No correlation as regards the number of days was observed from the first to the third vaccination and SARS-CoV-2 NT Abs/total IgG. The median level of SARS-CoV-2 NT Abs was 32-fold lower against Omicron compared to wild type strain (p = 0.0004) and 12-fold lower compared to Delta strain (p = 0.0110). Conclusions: The third dose is able to trigger both the humoral and the cell-mediated immune response in cancer patients on active treatment. Our preliminary data about the neutralization of the SARS-CoV-2 vaccine against variants of concern (VOCs) seem to confirm the vaccine lower activity.